THE COST REDUCTION - THE MAIN CONDITION FOR SUSTAINABLE DEVELOPMENT OF INDUSTRIAL ENTERPRISES - Vybornova, Valentina; Vybornova, Svetlana; Romanovich, Liudmila; Romanovich, Marina (Journal of Applied Engineering Science, 2014)
The deep and widespread changes in industry which are leads scientific-and-technological advance and systemic changes implemented in the course of from the global financial crisis, economic instability in the country and the world confront enterprise management tasks firm survival in difficult market conditions. As practice shows, the cornerstone of survivals- is a stationary state of company. The cornerstone is consider to entity ’s ability of the enterprise to pay obligations in full and on time , and be capable of self-financing of the projects planned for the development of the enterprise. Huge reserve to increase the financial stability of the enterprise carries the job of managing the cost of production. The cost reduction gives financial safety margin which can be used for development of the enterprise and to strengthen its market position.